(untitled) (Discourse of Law and Administration, 2023)
Public health is the guarantor of citizens’ health security, both on an individual and collective level. The aim of the article is to indicate the role of public health with the doctrinal and statutory assumptions, in combating infectious diseases and infections as well as functional problems of public health that emerged during the COVID-19 pandemic. The pandemic highlighted the state’s negligence in the area of public health, mainly in terms of procedures and institutional facilities established to prevent and combat infectious diseases. In Poland the role of public health is marginalized and the potential of specialists is not used.